Sytuacja ekonomiczna polskiej wsi w latach 2000-2008 - Kondratowicz-Pozorska, Jolanta (The Economic Situation of Polish Village between 2000 and 2008, 2009)
The paper presents characteristics of rural regions in scope of: chosen demographic factors, the economic activity of people, registered unemployment, income of village people, participation of farming in national economy. The author also defines directions and the level of investments in development of rural areas. The paper does not include all problems that are often observed in such regions.(original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 646-654